1987
DOI: 10.1002/ana.410210312
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis disease activity correlates with gadolinium‐enhanced magnetic resonance imaging

Abstract: Magnetic resonance imaging provides a method of visualizing multiple sclerosis plaques, but the age and activity of these plaques cannot be determined with routine magnetic resonance images. Gadolinium DTPA is a paramagnetic contrast agent that does not cross an intact blood-brain barrier. We studied 16 patients with multiple sclerosis, using magnetic resonance imaging, gadolinium-enhanced magnetic resonance imaging, and computed tomographic scans. Gadolinium enhancement of multiple sclerosis plaques correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

1989
1989
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(24 citation statements)
references
References 15 publications
0
22
0
2
Order By: Relevance
“…In the present study, lipids were detected as early as Day 10 in the acute plaques, but appeared more distinct after 2 or 3 months. The lipid formation is apparently delayed in comparison with blood-brain bamer (BBB) deficiency, which is the hallmark of active immunological disease (15,16). This may indicate that myelin degeneration, or at least production of free lipids, is a secondary phenomenon and not a primary pathogenic event in plaque formation.…”
Section: Figmentioning
confidence: 93%
“…In the present study, lipids were detected as early as Day 10 in the acute plaques, but appeared more distinct after 2 or 3 months. The lipid formation is apparently delayed in comparison with blood-brain bamer (BBB) deficiency, which is the hallmark of active immunological disease (15,16). This may indicate that myelin degeneration, or at least production of free lipids, is a secondary phenomenon and not a primary pathogenic event in plaque formation.…”
Section: Figmentioning
confidence: 93%
“…Brain MRI was abnormal in 70-95% of patients with definitive MS and the gadolinium enhancement correlated with the clinical activity of the disease and corresponded anatomically with the symptoms and signs (58). The evaluation of gadoliniumenhancing lesions is one MS MRI criteria for demyelination in time and space (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…Adams et al [12] suggested cerebral periphlebitis to be a precursor of plaque formations in surrounding tissues. A transitory breakdown of the bloodbrain barrier has been well documented at the time of dis ease activity by Tc-scintigraphy [13], CT scan [14], and more recently by MRI with gadolinium [15], Engell et al [16] found similar barrier damage in MS patients with PR, and analogous functional changes of the blood-retinal barrier during RP attacks, measured by vitreous fluorophotometry [ 17], Considering these simultaneous fea tures in the retina and the brain, and the similarity of their pathological aspects, it is reasonable to suppose a com mon etiopathogenesis for PR and CNS MS lesions, and to speculate that both ocular and cerebrum changes repre sent a primary phlebitic process that in the brain leads to demyelination, and in the retina, which is embryologically an extension of the CNS. stops at an early stage due to a lack of myelin in this site.…”
Section: Discussionmentioning
confidence: 99%